Hematological profiles of the Malayan sun bear (Heiarctos Malayanus) kept in captivity - Che Amat, Azlan; Arshad, Siti Suri; Hassan, Latiffah; Bahaman, Abdul Rani; Mat Naim, R.; Kevin, L. (Veterinary Association Malaysia, 2011)
Nineteen haematological parameters for the Malayan sun bear which include PCV, RBC count, differential counts for leucocytes, plasma protein, PT and APTT were evaluated. Twenty-six biochemical parameters were analysed namely sodium, potassium, chloride, inorganic phosphate, blood urea nitrogen, creatinine, glucose, cholesterol, total bilirubin, total protein, alanine transferase, alkaline phosphatase, aspartate aminotransferase, craetine kinase, globulin, albumin, globulin-albumin ratio, amylase, lactate dehydrogenase, lipase, lactate, uric acid, triglyceride and gammaglutamyl transferase. Comparing males and females, males showed a significantly higher value for haemaglobin. Leucocytes and segmented neutrophils were significantly higher in sub-adults. Current values showed low haemoglobin and leucocytes compared to previous data. Preliminary data on anticoagulation factors namely PT and APTT were recorded. Biochemistry showed ALT, GGT and CK were significantly higher in males. The sub-adult group showed higher values of ALT, GGT, CK, LDH and albumin. Compared to previous reports, current data showed lower values of calcium, inorganic phosphate, BUN and AST. Additional preliminary data on GGT, amylase, CK, total triglyceride, lipase and lactate were recorded.